Need for beta-blockade in hypertension reduced with long-term minoxidil. Issue 6134 (5th August 1978) - Brunner, H R; Jaeger, P; Ferguson, R K; Jequier, E; Turini, G; Gavras, H
Abstract : Sequential changes in plasma renin activity and urinary aldosterone and noradrenaline were assessed in eight patients with severe hypertension after minoxidil had been added to their treatment. Doses of 2.5--27.5 (mean 12.5) mg/day reduced the mean blood pressure from 166/113 +/-6/2 mm Hg to 124/88+/-4/2 mm Hg in one week. Plasma renin activity and urinary aldosterone and noradrenaline increased twofold to threefold initially but returned to baseline values within two to three weeks and remained unchanged during a mean follow-up of 5.1 months. Beta-blocking drugs were then withdrawn slowly in six patients without adverse effects, though blood pressure and heart rate increased in three patients, who required minimal doses of beta-blockers. Plasma renin activity and urinary aldosterone and noradrenaline did not change significantly after beta-blockade had been stopped. We conclude that the need for beta-blockade is greatly reduced with long-term minoxidil treatment and that it may be unnecessary in some patients.